(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
This research work presents the investigation on how poverty among parents influences the academicperformance of students in secondary schools in Anambra state, Nigeria. It was carried out infiveschools in Awka Education Zone of the State. This research question guided the research. The simplerandom sampling technique was adopted in gathering the relevant data using percentage as thestatistical method. Fifty questionnaires were administered. The study revealed among others that all students belong to a socio-economic class; it also revealed that students from poor parents are not well provided for with school uniform and learning materials and that student from lowincome parentsbehave better than those from high income parents. Recommended by the researcher is creationof jobopportunities by the non-governmental organization (NGOS), individuals and Government agencies. At all level, Government should encourage equal education opportunity to empower childrenfromlow income status.